Development and validation of the Thai risk screening questionnaire to screen the visual problem of the older adults in Thailand - Yingyong, Penpimol (Journal of Public Health and Development, 2018)
Screening the risk of the visual problem in older adults has never been developed in Thailand. It is the necessary for primary public health care policy to support the local personnel (at the grass root level) who can thoroughly use the medical services to screen the risky rural patients. This study aimed to translate and evaluate the quality of the Thai version of the visual problem in older adults as the risk screening questionnaire. The original screening questionnaire by Horowitz, et al(1991) was translated and modified into the Thai version. The Thai version of questionnaires was primarily used with 450 participants as part of pre-testing between October 2016 to March 2017. Out of these, 225 were visually impaired patients attended at the out-patient eye clinic in the hospital and 225 ones without visual impairment. The results showed specificity of 75.1%, sensitivity of 93.8%, positive and negative likelihood ratios of 3.77 and 0.08. The positive and negative predictive value were 79.0% and 92.4% respectively. Its accuracy was 84.4%. The study indicated that the Thai version of the visual problem in the Thai older adults risk screening questionnaire showed high accuracy in detecting visual impairments and should be suitable to use as the screening tool in the primary care setting.